2010
DOI: 10.3855/jidc.1261
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular catheter-related infections in an Indian tertiary care hospital

Abstract: Introduction: This study had two objectives: 1) to determine the clinical and microbiological profiles of patients developing intravascular catheter-related local (localized catheter colonization and exit site) and systemic infections and their predisposing factors; 2) to study the antibiotic sensitivity patterns of the organisms isolated. Methodology: This case-control study was conducted over 19 months involving 232 patients at a tertiary care hospital. Non-tunneled central venous catheters and midline cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 27 publications
5
52
1
1
Order By: Relevance
“…Other studies also showed male predominance like the study done by H.V Patil [19] which showed 59% males and 41% females were affected, the study done by Deepti et al [15] showed 69% males and 31% females affected, the study done by Daniela Bicudo [17] showed 58.85 males and 41.2% females affected and the study by Ramanathan Parameswaran et al [16] showed 72% males and 28% females were affected. CRBSI rates were high in all these studies because of associated or predisposing factors which were seen more in males like smoking, alcohol intake and comorbid illness like HTN, DM, ketoacidosis bronchial asthma, COPD, renal failure, patient on immune suppressive therapy, chemotherapy, etc.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Other studies also showed male predominance like the study done by H.V Patil [19] which showed 59% males and 41% females were affected, the study done by Deepti et al [15] showed 69% males and 31% females affected, the study done by Daniela Bicudo [17] showed 58.85 males and 41.2% females affected and the study by Ramanathan Parameswaran et al [16] showed 72% males and 28% females were affected. CRBSI rates were high in all these studies because of associated or predisposing factors which were seen more in males like smoking, alcohol intake and comorbid illness like HTN, DM, ketoacidosis bronchial asthma, COPD, renal failure, patient on immune suppressive therapy, chemotherapy, etc.…”
Section: Discussionmentioning
confidence: 98%
“…This is comparable to the National Nosocomial Infection Surveillance (NNSI) System report (2 to 11.3 per 1000 catheter days). [13] Similarly, CRBSI rate in the study of S. Singh et al [14] showed 0.48 per 1000 catheter days, Deepti et al [15] showed 8.2 per 1000 catheter days, Ramanathan Parameswaran et al [16] was 8.75 per 1000 catheter days, Daniela Bicudo [17] showed 10.22 per 1000 catheter days, M. Kaur [18] showed 14.59 per 1000 catheter days, Harsha V Patil [19] showed 47.31 per 1000 catheter days. Total 150 catheter samples included in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may help to reduce the unnecessary use of antibiotics. Parameswaran et al, reported that MDR microbes caused 30.2% of the catheter-related blood-stream infections and empirical treatment had no role in prevention of such infections [29]. This mandates use of aseptic protocol to minimize local or systemic infections associated with any procedures.…”
Section: Role Of Pharmacistmentioning
confidence: 99%